IMPROVEMENT OF FORAGE MANAGEMENT FOR BALI CATTLE IN SOUTH SULAWESI - S Bahar; A. Natsir (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2011)
One factor affecting productivity of bali cattle is availability of good quality forages. Based on that reason, Australian Centre for Internatioanal Agriculture Research (ACIAR) in cooperation with Hasanuddin University and BPTP of South Sulawesi funded a program with an aim to improve forage management for bali cattle in South Sulawesi. This activity was carried out under farm condition involving sixty “best-bet” farmers in twelve villages across three districts (Barru, Bone and Gowa). Aspects evaluated in this program were utilization of existing forages and utilization of new forages by the farmers. In addition, sufficiency of forage for the cattle of best bet farmers was also evaluated. The results indicated that before implementation of ACIAR program, the average proportion of forage used by the farmers to feed on the cattle was 43.4% elephant grass, 34.4% native grass, 12.6% peanut straw/maize stover, 9.1% rice straw, and 0.7% tree legumes. After program implementation, there was a change in the proportion of forage for cattle, namely 47.3% elephant grass, 13.4% native grass, 12.4% peanut straw/maize stover, 12.3% rice straw, 4.1% tree legume leaves. Proportion of some new forages used by the farmers was 2.1% setaria, 2.5% mulato, 5.1% paspalum, and 0.9% panicum. In conclusion, there was a different in the proportion of forages used by the farmers to feed on the cattle before and after project implementation, in which the proportion of elephant grass and tree legume leaves increased and decreased in the use of native grass, while use of agricultural byproduct was relatively stable. In terms of utilization of new grasses introduced, paspalum was the most popular grass for best bet farmer to feed on the cattle.